Effect of stereoregularity on excitation‐dependent fluorescence and room‐temperature phosphorescence of poly(2‐vinylpyridine). Issue 2 (4th October 2022) - Du, Hongxu; Zhao, Wenjing; Xia, Yijie; Xie, Siyu; Tao, Yi; Gao, Yi Qin; Zhang, Jie; Wan, Xinhua
Abstract: Preparation of non‐conjugated luminescent polymers (NCLPs) with excellent cluster luminescence (CL) performance is of great significance for scientific and industrious applications, and yet improving the performance of NCLPs through proper structural design is still a huge challenge. Herein, we report a non‐conjugated ionized polymeric system consisting of (−)‐camphorsulfonic acid ((−)‐CSA) and poly(2‐vinylpyridine) (P2VP). These acid‐base complexes exhibit typical excitation‐dependent fluorescence and room‐temperature phosphorescence (RTP) with a lifetime up to 364 ms. We discover that changing the stereoregularity from atactic to isotactic significantly improves the CL performance of the complex. It (1) broadens the fluorescence emission spectra to cover the entire visible region, (2) enhances the fluorescence emission intensity at long wavelength beyond 500 nm, (3) enhances the phosphorescence intensity, and (4) extends the phosphorescence lifetime. Systematical experimental characterization and molecular dynamics simulation unravel the key role of stereoregularity in determining the formation of different pyridine aggregates that strongly influence the CL performance. Moreover, the different luminescence shows great potential in excitation divided information display and time‐resolved encrypted display. This work not only points to a new direction for developing NCLPs with excellent performance, but also broadens the applications of NCLPs materials. Abstract : A non‐conjugated ionized polymeric complex consisting of (−)‐camphorsulfonic acid and poly(2‐vinylpyridine) is synthesized. This complex exhibits excitation‐dependent fluorescence and room‐temperature phosphorescence. Changing the stereoregularity of polymeric main chain from atactic to isotactic significantly improves the cluster luminescence performance, including the broad range of fluorescence emission, the enhanced fluorescence and phosphorescence intensities, and prolonged phosphorescence lifetimes.